A 6-year single-center prospective follow-up study of the efficacy of radiofrequency ablation for thyroid nodules - Chuanke, Shi; Ming, Luo; Zhideng, Yan; Huan, Liu (Frontiers in Endocrinology, 2024)
Background: Radiofrequency ablation (RFA) is an alternative modality for thyroid nodules (TNs) and many studies have also confirmed its favorable efficacy and safety. The scope of RFA increases in clinical practice and the aim of our study was to evaluate the efficacy of RFA.Methods: We conducted a prospective study to evaluate the efficacy of RFA for thyroid nodules between January 2017 and December 2022 at our institution. We assessed the change in nodal volume, volume reduction ratio (VRR), technique effective (TE) rate, complete ablation (CA) rate, and nodal regrowth rate and time after RFA.Results: We performed RFA for 1703 patients with TNs between January 2017 and December 2022, of which a total of 970 eligible patients were enrolled in the study. The preoperative volume of TNs was 6.23 ± 8.11ml, with 821 benign and 149 malignant nodules. The post-RFA TE and adjusted TE rate were 80% and 88.8%, respectively. CA was achieved in 145 (14.9%) patients with a mean time of 18.32± 12.98 months; nodal regrowth occurred in 15(1.5%) patients with a mean time of 29.80 ± 12.47 months. TNs volume and VRR changed significantly at years 1 and 2 after RFA and stabilized after 5 years. A serious postoperative adverse event occurred in one patient with cervical sympathetic chain injury resulting in Horner's syndrome. A transient or permanent damage of the recurrent laryngeal nerve could not be evaluated due to the lack of postoperative laryngoscopy, and this is a significant limitation of the study.The expanded RFA indications were also effective for TNs, with no significant change in long-term efficacy.